The Acquisition of /r/ in Iraqi Arabic - Mohammed, Fuad Jassim (Al-Adab Journal, 2022)
There is very little research in the field of Arabic language acquisition This study explores the development in the acquisition of the trill /r/ in Iraqi Arabic (IA). It attempts to answer four main questions: (1) What percentage in the total sample produced /r/ correctly? (2) Is this the age of customary, acquisition, or mastery for IA children? (3) Does the production accuracy of /r/ vary by position in the syllable and child sex? (4) How is the acquisition of /r/ developed within this age group? Samples were collected from 20 normally developing children between the ages of 1:8 and 3:7. The results showed noticeable sex differences in the acquisition of /r/. Besides, /r/ was produced more accurately in syllable-initial than syllable-final position. Statistics reflected a cross-dialectal variation among Arabic dialects, where Iraqi children acquired /r/ at different age it is acquired in other Arabic dialects, such as Jordanian Arabic. However, results of this paper go in support of previously suggested universal sound acquisition as /r/ was acquired in IA at about the same age it is acquired in English. The acquisition of /r/ was accompanied by gliding and deletion.